التكيف المدرسي وعلاقته بالدافعية للإنجــاز لــدى تلاميــذ السنــة أولى ثــانـوي - بشيري, بلال (جامعة الوادي university of Eloued, 2022)
ملخص الدراسة: تهدف هذه الدراسة إلى محاولة التعرف على علاقة التكيف المدرسي بالدافعية للإنجاز لدى تلاميذ سنة أولى ثانوي لشعبتي جذع مشترك آداب وجذع مشترك علوم وتكنولوجيا بثانوية كركوبية خليفة بولاية الوادي. وللإجابة على التساؤل التالي: هل توجد علاقة إرتباطية ذات دلالة إحصائية بين التكيف المدرسي والدافعية للإنجاز لدى تلاميذ السنة الأولى ثانوي؟ وقد تم الإعتماد في هذه الدراسة على المنهج الوصفي الإستدلالي مستخدمين أداتين لجمع البيانات هما: مقياس التكيف المدرسي، ومقياس الدافعية للإنجاز لكعبوش حكيمة (2018)، حيث أجريت الدراسة على عينة عشوائية طبقية مكونة من (100) تلميذ وتلميذة تم إختيارهم بالطريقة العشوائية المنتظمة، أما بالنسبة للمعالجة الإحصائية فتمت عن طريق تطبيق البرنامج الإحصائي (SPSS)، وتم الإعتماد على إختبار تحليل التباين (f) للكشف عن دلالة الإرتباط بين التكيف المدرسي والدافعية للإنجاز، و إختبار ( ت Ttest) لعينتين مستقلتين، للكشف عن دلالة الفروق بين تلاميذ السنة الأولى ثانوي، على مقياسي التكيف المدرسي والدافعية للإنجاز تبعاً للجنس (ذكور/إناث) والشعبة الدراسية (جذع مشترك آداب/جذع مشترك علوم وتكنولوجيا). وقد أسفرت الدراسة على النتائج التالية: - توجد علاقة إرتباطية دالة إحصائياً بين التكيف المدرسي والدافعية للإنجاز لدى تلاميذ السنة الأولى ثانوي. - لا توجد فروق بين الذكور والإناث من تلاميذ السنة الأولى ثانوي على مقياس التكيف المدرسي. - لا توجد فروق بين الذكور والإناث من تلاميذ السنة الأولى ثانوي على مقياس الدافعية للإنجاز. - لا توجد فروق بين تلاميذ السنة الأولى ثانوي على مقياس التكيف المدرسي تبعاً للشعبة الدراسية (جذع مشترك آداب/جذع مشترك علوم وتكنولوجيا). - لا توجد فروق بين تلاميذ السنة الأولى ثانوي على مقياس الدافعية للإنجاز تبعاً للشعبة الدراسية (جذع مشترك آداب/جذع مشترك علوم وتكنولوجيا).   Study summary: This study aims to try to identify the relationship of school adaptation to the motivation for achievement among students of the first year of secondary school for the two divisions of a common trunk of arts and a common trunk of science and technology at Karkoubia Khalifa High School in El-Wadi State. And to answer the following question: Is there a statistically significant correlation between school adaptation and achievement motivation among first year secondary students? The descriptive and inferential approach was relied upon using two tools to collect data, namely: the school adaptation scale, and the achievement motivation scale by Kaabush Hakima (2018), where the study was conducted on a stratified random sample of (100) male and female students who were chosen by the systematic random method, as for the statistical treatment It was done by applying the SPSS statistical program, and the analysis of variance (f) test was relied upon to reveal the significance of the correlation between school adaptation and achievement motivation, and the T-test for two independent samples, to reveal the significance of the differences between first year secondary students, on the two scales of school adaptation. And the motivation for achievement according to gender (males/females) and the academic division (a common trunk of literature/a common trunk of science and technology). The study resulted in the following results: - There is a statistically significant correlation between school adaptation and achievement motivation among first year secondary students. - There are no differences between male and female first year secondary students on the school adaptation scale. - There are no differences between males and females of the first year secondary school students on the achievement motivation scale. - There are no differences between first-year secondary students on the school adaptation scale according to the academic division (common trunk of literature / common trunk of science and technology). - There are no differences between first year secondary students on the achievement motivation scale according to the academic division (a common trunk of literature / a common trunk of science and technology).
دراسة ميدانية بثانوية كركوبية خليفة بدائرة الرباح - ولاية الوادي
مذكرة ماستر علم النفس تخصص علم النفس المدرسي
Keywords: التكيف المدرسي، الدافعية للإنجاز; Adaptation scolaire, motivation à réussir; School adaptation, achievement motivation